Investigation of spatial and temporal variability of site response in the Arunachal Himalaya using ambient seismic noise and earthquake waveforms. Issue 4 (23rd June 2019) - Singh, A.P.; Kumar, M. Ravi; Pandey, Abhay; Roy, Ketan Singha
ABSTRACT: The Arunachal region that constitutes the easternmost segment of the Himalaya has experienced two great earthquakes in the past. This portion is geologically and seismo‐tectonically unique compared to the other parts of Himalaya. In this study, the ambient seismic noise and earthquake waveforms registered at 34 broadband seismograph stations with a flat frequency response between 120 and 0.02 seconds are analysed to understand the stability and reliability of the horizontal‐to‐vertical spectral ratio method. Also, we use the bootstrapping method to estimate the uncertainty and variations in the horizontal‐to‐vertical spectral ratio in different seasons. Although the predominant frequency does not show any seasonal variation, the amplitudes reveal a slight dependence. The predominant frequencies in the area mainly vary from 1.1 to 7.0 Hz. At a few sites, two peaks well separated in frequency, indicate shallower and deeper structures with impedance contrast. Our results show that the average predominant frequencies are around 3.5 Hz for the undifferentiated granite gneiss, 4.3 Hz for the Bomdila granite gneiss, 2.1 Hz for the Bomdila group of rocks (Paleoproterozoic), 2.8 Hz for the Gandise batholiths, 2.6 Hz for the Gondwana succession and 1.8 Hz for the Abor formation. The amplification estimated by the site‐to‐reference method varies between 1.5 and 6.2, which is lower than that obtained from the HVSR method. Validation of the results from ambient seismic noise was performed by comparing them with those from the earthquake waveforms and correlation with local geology.